1982
DOI: 10.1111/j.1365-2494.1982.tb01572.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of variety, cutting interval and nitrogen application on the morphology and development of stolons and leaves of white clover

Abstract: Six varieties of white clover, each grown with perennial ryegrass, four intervals between cuts and two levels of applied nitrogen in all combinations, were compared in a field experiment during the first 27 months after sowing. Information about yields, crop fractions, heights and ryegrass tillers has been presented in an earlier paper (Wilman and Asiegbu, 1982). The present paper is concerned with the more detailed studies of white clover, which help to explain the yield results and contribute to the understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 11 publications
(20 reference statements)
6
31
0
Order By: Relevance
“…Observations made during this study confirm and extend those of Wilman & Asiegbu (1982) in that stolon death progressing towards the tip often stopped at the point of rooting of a node in both buried and surface stolons. Also, death of buried stolons was sometimes seen to cease at the point where a vertical growing branch stolon was initiated.…”
Section: Observations and Photographssupporting
confidence: 69%
“…Observations made during this study confirm and extend those of Wilman & Asiegbu (1982) in that stolon death progressing towards the tip often stopped at the point of rooting of a node in both buried and surface stolons. Also, death of buried stolons was sometimes seen to cease at the point where a vertical growing branch stolon was initiated.…”
Section: Observations and Photographssupporting
confidence: 69%
“…Although the strong correlation between total leaf production and unit stolon weight does not prove a causal relationship, this is possible and needs to be researched. Few investigations have measured cultivar differences in stolon thickness or weight but the results of Wilman & Asiegbu (1982) and Harris Rhodes & Mee (1983) show clearly the larger diameter and weight per unit length, respectively, of stolons grown by largeleaved white clovers. However, stolons are generally below grazing or cutting height and, apart from perhaps supporting the growth of large leaves, do not themselves contribute to herbage yield unless grazing is particularly severe.…”
Section: Leaf Longevitymentioning
confidence: 99%
“…It is well understood that increasing frequency ofdefoliation, as occurs under set-stocking, reduces leaf size and petiole length (Wilman & Asiegbu 1982). Lambert et al (1986) also observed that leaf size of white clover in rotationally grazed cattle swards were larger than those in swards either setstocked or rotationally grazed by sheep.…”
Section: Comparison Of Hill Countrygenotypes With (Grasslands Huia' Amentioning
confidence: 98%